Development and Validation of an Indonesian Questionnaire for Assessing Paracetamol Self-Medication Knowledge, Attitude, and Practice - Putri, Widyana Sagita; Sauriasari, Rani; Septyowati, Priharika (Kesmas, 2026)
Paracetamol is a widely used over-the-counter medicine for self-medication and is often perceived as completely safe. However, inappropriate use may result in hepatotoxicity and other adverse effects, particularly at high doses. This study aimed to develop and validate a questionnaire to assess the general Indonesian population’s knowledge, attitude, and practice (KAP) regarding paracetamol self-medication. The validation procedure consisted of three stages: content, face, and construct validation. Three experts assessed the relevance of the items using the Content Validity Index, and five respondents were interviewed to assess the linguistic clarity and comprehensibility of the questions. Construct validity and reliability were assessed in 30 participants using Pearson’s correlation and Cronbach’s alpha. All items obtained excellent relevance scores. The final questionnaire demonstrated acceptable validity and reliability after revising and removing two low-performing practice items (P3 and P4), with Pearson’s correlation coefficients exceeding the r-table threshold (0.361) and Cronbach’s alpha values of 0.766, 0.734, and 0.640 for the KAP domains, respectively. The final instrument, comprising 20 items (10 knowledge items, 6 attitude items, and 4 practice items), was deemed suitable for assessing public KAP regarding safe self-medication with paracetamol.